Hubungan Manajemen Stres Terhadap Kinerja Pegawai di Kantor Camat Talang Kelapa Kabupaten Banyuasin - Tia Firda Agustin; Lena Marianti (CV. ITTC INDONESIA, 2025)
This study aims to determine the relationship between stress management and employee performance at the Talang Kelapa Sub-district Office, Banyuasin Regency. The background of the study is based on the phenomenon of increasing work pressure due to administrative burdens, public service demands, and dynamic work environment conditions that have the potential to cause stress if not managed effectively. The research method used is a quantitative approach with a survey technique, where data is collected through distributing questionnaires to employees and analyzed using a correlation test to see the closeness of the variable relationship. The results show that stress management has a significant relationship with employee performance. Employees who are able to manage stress well tend to show more optimal performance, characterized by increased discipline, work effectiveness, service to the community, and the ability to complete tasks on time. Conversely, unmanaged stress can reduce motivation, cause emotional exhaustion, and negatively impact productivity. Thus, this study emphasizes the importance of implementing stress management strategies in the workplace through training, leadership support, and the creation of a healthy work climate. These efforts are expected to improve the quality of employee work while improving the quality of public services at the Talang Kelapa Sub-district Office, Banyuasin Regency.